The Utilization of Gleason Grade as the Primary Criterion for Ordering Nuclear Bone Scan in Newly Diagnosed Prostate Cancer Patients - Chad W. M. Ritenour; John T. Abbott; Michael Goodman; Naomi Alazraki; Fray F. Marshall; Muta M. Issa (The Scientific World Journal)
Utilization of nuclear bone scans for staging newly diagnosed prostate cancer has decreased dramatically due to PSA-driven stage migration. The current criteria for performing bone scans are based on limited historical data. This study evaluates serum PSA and Gleason grade in predicting positive scans in a contemporary large series of newly diagnosed prostate cancer patients. Eight hundred consecutive cases of newly diagnosed prostate cancer over a 64-month period underwent a staging nuclear scan. All subjects had histologically confirmed cancer. The relationship between PSA, Gleason grade, and bone scan was examined by calculating series of crude, stratified, and adjusted odds ratios with corresponding 95% confidence intervals. Four percent (32/800) of all bone scans were positive. This proportion was significantly lower in patients with Gleason score ≤7 (1.9%) vs. Gleason score ≥8 (18.8%, p < 0.001). Among patients with Gleason score ≤7, the rate of positive bones scans was 70-fold higher when the PSA was >30 ng/ml compared to ≤30 ng/ml (p < 0.001). For Gleason score ≥8, the rate was significantly higher (27.9 vs. 0%) when PSA was >10 ng/ml compared to ≤10 ng/ml (p = 0.002). The combination of Gleason score and PSA enhances predictability of bone scans in newly diagnosed prostate cancer patients. The PSA threshold for ordering bone scans should be adjusted according to Gleason score. For patients with Gleason scores ≤7, we recommend a bone scan if the PSA is >30 ng/ml. However, for patients with a high Gleason score (8–10), we recommend a bone scan if the PSA is >10 ng/ml.